Valoriser l’écologie pour légitimer le paysage ? - Fabien Roussel (EchoGéo)
The surrounding vegetation of Paris metropolis – a time concerned by a green belt project – is concerned by multiple “green” developments, varying in size and focusing on ecological issues. This article crosses literature sources, photography analysis and landscape sketches to show how these ecological values actually legitimize landscape values. These are illustrated by the representations from traveling writers, which reflect the urban imaginary of rural nature. Photography analysis shows that ecological valuation by the stakeholders not only depends on ecological qualities of habitats but also on uses and practises. Eventually, sketches reveal the landscape dimension of the vegetation around Paris, and thus question stakeholder’s intentions in given territorial contexts.